Facilitating masked visual target identification with auditory oddball stimuli. - Ngo, M; Spence, C (2012)
When identifying a rapidly masked visual target display in a stream of visual distractor displays, a high-frequency tone (presented in synchrony with the target display) in a stream of low-tone distractors results in better performance than when the same low tone accompanies each visual display (Ngo and Spence in Atten Percept Psychophys 72:1938-1947, 2010; Vroomen and de Gelder in J Exp Psychol Hum 26:1583-1590, 2000). In the present study, we tested three oddball conditions: a louder tone presented amongst quieter tones, a quieter tone presented amongst louder tones, and the absence of a tone, within an otherwise identical tone sequence. Across three experiments, all three oddball conditions resulted in the crossmodal facilitation of participants' visual target identification performance. These results therefore suggest that salient oddball stimuli in the form of deviating tones, when synchronized with the target, may be sufficient to capture participants' attention and facilitate visual target identification. The fact that the absence of a sound in an otherwise-regular sequence of tones also facilitated performance suggests that multisensory integration cannot provide an adequate account for the 'freezing' effect. Instead, an attentional capture account is proposed to account for the benefits of oddball cuing in Vroomen and de Gelder's task.